Environmental context shapes the long‐term role of nutrients in driving producer community trajectories in a top–down dominated marine ecosystem. (4th June 2020) - Clausing, Rachel J.; Phillips, Nicole E.; Fong, Peggy
Abstract: Two predominant anthropogenic impacts on ecosystems, nutrient enrichment and the removal of consumers, are predicted to interact in their effects on producer diversity. Yet, measures of diversity alone may not capture changes occurring in the underlying mechanisms structuring communities. Furthermore, evidence for these interactions in rocky intertidal systems is mixed and may be confounded by variable baseline productivity or short experimental durations that do not capture seasonality, environmental heterogeneity or successional processes. We conducted a 2‐year experiment examining the main and interactive effects of nutrients and herbivores in a low‐productivity environment on the northern shore of Cook Strait near Wellington, New Zealand. We explicitly accounted for the small‐scale spatial environmental heterogeneity characteristic of rocky shores. Rapid and dramatic shifts in diversity metrics and cover of algal communities in the first year were driven by removal of herbivores. Within 2 months of herbivore exclusion, open space decreased from >90% to <15%, regardless of nutrient addition, and both algal diversity and evenness plummeted while species richness rose. In contrast to theoretical predictions, strong interactions between top–down and bottom–up forces on diversity were rare; rather, over time, the addition of nutrients negatively impacted diversity. Further, where herbivores were removed, nutrients inhibited succession beyond ephemeral forms, contrasting with the tolerance model of succession observed under ambient nutrients. The effects of nutrients were only elucidated by accounting for variation in habitat complexity and seasonality, demonstrating that environmental heterogeneity can mask bottom–up processes. Moreover, shifts in relative species abundances revealed that after 10 months, nutrient addition caused increased community turnover regardless of herbivore presence or absence, indicating reduced stability not apparent in simple measures of diversity. Synthesis . Our results suggest that nutrient addition and herbivore reduction exert strong but mostly independent control on community biodiversity, where context dependency in habitat complexity, seasonality and successional stage played key roles in determining community outcomes. These findings demonstrate the importance of longer‐term field studies incorporating environmental context and multiple metrics of diversity to reveal the mechanisms underlying effects of nutrient enrichment and herbivore loss on producer community structure. Abstract : Our study shows that in a strongly top–down controlled marine ecosystem, changes in nutrient availability can still shape community development through effects on species composition and turnover, even in the absence of strong effects on traditional diversity measures. Evidence that environmental variability can mask these bottom–up processes highlights the importance of longer‐term field studies incorporating environmental context and multiple metrics of diversity to clarify resource and consumer relationships with producer community structure and function.